The Role of Social Networking Sites in Improving Linguistic Communication Skills among Students at the Open Arab University of Jordan - Mistareehi, Hussein Hikmat (Dirasat: Human and Social Sciences, 2025)
Objectives: The purpose of this study is to examine the role of social communication sites in improving the linguistic communication skills of students at the Open Arab University of Jordan. Methods: The survey methodology was followed, with students randomly selected from the Open Arab University of Jordan participating in the study. They were asked to complete a survey identifying their linguistic communication skills. The results revealed that social communication sites contributed to the improvement of combined medium-sized language, communication skills, hearing skills, reading skills, and highly modern skills. Written skills, rules and dictates, medium-level communication, and literary taste were also evaluated. Results: The results showed no differences due to variables such as gender, scientific qualification, school year, and social situation. However, differences were found based on the type of college, favoring scientific faculties. Conclusions: The study recommended designing social networking sites related to the linguistic aspect and using them to improve the linguistic communication skills of university students.